2022
DOI: 10.3389/fmicb.2022.831852
|View full text |Cite
|
Sign up to set email alerts
|

The CREB and AP-1–Dependent Cell Communication Network Factor 1 Regulates Porcine Epidemic Diarrhea Virus-Induced Cell Apoptosis Inhibiting Virus Replication Through the p53 Pathway

Abstract: Porcine epidemic diarrhea virus (PEDV) infection causes severe diarrhea, dehydration, and high mortality in sick pigs, causing huge economic losses to the pig industry. However, the relationship between cell communication network factor 1 (CCN1) and PEDV infection has not been reported. In this study, we showed that the expression of CCN1 was enhanced by PEDV infection, and we observed that PEDV promotes the CREB and AP-1 activation to promote CCN1 expression. The PKA and p38 inhibitors significantly suppress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In response to ER stress, high expression of CHOP promotes caspase activation through the upregulation of the proapoptotic protein Bax and downregulation of the antiapoptotic protein Bcl-2, leading to apoptosis. Our previous studies have shown that PEDV infection induces the initiation of intrinsic apoptosis pathways [ 12 , 32 ]. Our present study indicates that overexpression of H2BE promotes PEDV replication, downregulates CHOP expression in the PERK, eIF2, IRE1, and JNK pathways, decreases the expression of Bax, cleaved caspase-9 and cleaved caspase-3 and increases the expression of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to ER stress, high expression of CHOP promotes caspase activation through the upregulation of the proapoptotic protein Bax and downregulation of the antiapoptotic protein Bcl-2, leading to apoptosis. Our previous studies have shown that PEDV infection induces the initiation of intrinsic apoptosis pathways [ 12 , 32 ]. Our present study indicates that overexpression of H2BE promotes PEDV replication, downregulates CHOP expression in the PERK, eIF2, IRE1, and JNK pathways, decreases the expression of Bax, cleaved caspase-9 and cleaved caspase-3 and increases the expression of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV inhibits apoptosis by suppressing the expression of CHOP/DDIT3 [ 11 ]. Our previous studies have shown that CCN1 inhibits viral replication by promoting PEDV-induced apoptosis via the mitochondrial pathway [ 12 ]. However, the mechanism by which apoptosis affects PEDV replication is not completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of PEDV replication in Marc-145 cells showed that the viral RNA levels peaked at 48 hpi and decreased thereafter [ 41 ].Therefore, the samples from 24 and 48 hpi were selected for RNA sequencing. MARC-145 cells were divided into three groups: cells infected with PEDV for 24 h (S24hpi_1, 2, 3), cells infected with PEDV for 48 h (S48hpi_1, 2, 3), and mock-infected cells as controls (Mock_1, 2, 3).…”
Section: Methodsmentioning
confidence: 99%
“…These ISGs enhance the recruitment and activation of FADD. FADD is an adaptor molecule that transmits apoptotic signals from death receptors on the cell surface, such as the TRAIL receptors to initiate the caspase cascade [14][15][16].…”
Section: Extrinsic Pathwaymentioning
confidence: 99%